Carbon and hydrogen stable isotope fractionation associated with the anaerobic degradation of propane and butane by marine sulfate‐reducing bacteria. (12th September 2013) - Jaekel, Ulrike; Vogt, Carsten; Fischer, Anko; Richnow, Hans‐Hermann; Musat, Florin
Summary The anaerobic degradation of propane and butane is typically initiated by activation via addition to fumarate. Here we investigated the mechanism of activation under sulfate‐reducing conditions by one pure culture (strain BuS5) and three enrichment cultures employing stable isotope analysis. Stable isotope fractionation was compared for cultures incubated with or without substrate diffusion limitation. Bulk enrichment factors were significantly higher in mixed vs. static incubations. Two dimensional factors, given by the correlation of stable isotope fractionation of both carbon and hydrogen at their reactive positions (Lambda reactive position, Λrp), were compared to analyse the activation mechanisms. A characteristic reactive position isotope fractionation pattern was observed, distinct from aerobic degradation. Λrp values ranged from 10.5 to 11.8 for propane and from 7.8 to 9.4 for butane. Incubations of strain BuS5 with deuterium‐labelled n‐alkanes indicated that butane was activated solely at the subterminal C atom. In contrast, propane was activated mainly at the subterminal C atom but also significantly at the terminal C atoms. A conservative estimate suggests that about 70% of the propane activation events occurred at the subterminal C atom and about 30% at the terminal C atoms.